Information System For Receiving Inpatients For Covid-19 Cases - Siska Decahyati; Faras Prascellia Carmalita; Meira Hidayati; Candra Mecca Sufyana (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
Coronavirus (Covid-19) cases are increasing now and it makes the hospital should be ready to receive patients. The problems faced made the queues of patients mixed up, between general patients and Covid-19 cases, which overwhelmed the officers in serving. So it should be a must for the hospital to upgrade the system of inpatient administration, especially for Covid-19 patients. The information system of inpatient administration for Covid-19 cases has become a very important thing to simplify the performance of officers, make reports easier to be more computerized, and simplify the administrative process to be easier and more efficient. The research method of this research is done by interview and observation, where the information system development is using the design uses data flow diagrams with the implementation of visual studio 2010 programming language and the database is using Microsoft Access. based on the results obtained from Covid-19 inpatient admission system, the system input consists of log-in form, new patient data entry form, inpatient registration form, and doctor form. Testing using the Black box, which results in a successful test for each form. The test results in the input that generates an as-expected output. The design has created an information system for receiving inpatients for COVID-19 cases according to needs which are obtained from the interview with the IGD registration officer at the hospital "X" in Bandung. This information system is very helpful for hospital management and improves the quality of service of the hospital.